Kinetics of the barotropic ripple (P beta')/lamellar liquid crystal (L alpha) phase transition in fully hydrated dimyristoylphosphatidylcholine (DMPC) monitored by time-resolved x-ray diffraction. - CAFFREY, MARTIN (My University, 1991)
We present here the first study of the use of a pressure-jump to induce the ripple (P,.)/lamellar liquid crystal (Lj phase transition in fully hydrated 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC). The transition was monitored by using time-resolved x-ray diffraction (TRXRD). Applying a pressure-jump from atmospheric to 11.3 MPa (1640 psig, 11 1.6 atm) in 2.5 s induces the La to P,. phase transition which takes place in two stages. The lamellar repeat spacing initially increases from a value of 66.0 ? 0.1 A (n = 4) to a maximum value of 70.3 + 0.8 A (n = 4) after 10 s and after a further 100-150 s decreases slightly to 68.5 + 0.3 A (n = 4). The reverse transition takes place following a pressure jump in 5.5 s from 11.3 MPa to atmospheric pressure. Again, the transition occurs in two stages with the repeat spacing steadily decreasing from an initial value of 68.5 + 0.3 A (n = 3) to a minimum value of 66.6 + 0.3 A (n = 3) after 50 s and then increasing by - 0.5 A over a period of 100 s. The transition temperature increases linearly with pressure up to 14.1 MPa in accordance with the Clapeyron relation, giving a dT/dP value of 0.285?C/MPa (28.50C/kbar) and an associated volume change of 40 ,ul/g. A dynamic compressibility of 0.13 + 0.01 AkMPa has been determined for the La phase. This value is compared with the equilibrium compressibilities of bilayer and nonbilayer phases reported in the literature. The results suggest testable mechanisms for the pressure-induced transition involving changes in periodicity, phase hydration, chain order, and orientation. A more complete understanding of the transition mechanism will require improvement in detector spatial resolution and sensitivity, and data on the pressure sensitivity of phase hydration.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; x-ray diffraction